A proposed testbed for detector tomography - Coldenstrodt-Ronge, H; Lundeen, J; Pregnell, K; Feito, A; Smith, B; Mauerer, W; Silberhorn, C; Eisert, J; Plenio, M; Walmsley, I (2009)
Measurement is the only part of a general quantum system that has yet to be characterised experimentally in a complete manner. Detector tomography provides a procedure for doing just this; an arbitrary measurement device can be fully characterised, and thus calibrated, in a systematic way without access to its components or its design. The result is a reconstructed POVM containing the measurement operators associated with each measurement outcome. We consider two detectors, a single-photon detector and a photon-number counter, and propose an easily realised experimental apparatus to perform detector tomography on them. We also present a method of visualising the resulting measurement operators.